Revitalization of the Guardhouse as a Community Security Building in RT 04 of Wisma Permai Housing - Ziliwu, Kharisma; Gentario, Daniel; Hondo, Seanivenna F.; Boli, Ferdinard; Setiadi, Widriyakara; Roosandriantini, Josephine; Hidayat, Anas (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research explores revitalization, focusing on the transformation of an idle guardhouse in the Wisma Permai Mulyorejo Surabaya housing complex into a functional community security asset. It underscores the importance of such projects in community security and urban planning. Method: The study employs the ANSOS (Assessment, Needs Analysis, Solution, Output, and Sustainability) method to guide the revitalization process of the guardhouse in RT 04. This methodology encompasses various stages, including comprehensive field surveys, interviews, questionnaires, the development of alternative guardhouse designs, and the facilitation of Forum Discussion Groups (FGD). Practical Applications: Successful revitalization can enhance security and generate economic value by repurposing the guardhouse. The findings inform urban planning and community development. Conclusion: This research aims to revitalize the dormant guardhouse in Wisma Permai, creating a functional community security hub. The results offer improved security and economic benefits, contributing to urban development knowledge.